Child Protective Services and University-Based Partnerships: A Participatory Action-Based Model for Creating and Sharing Knowledge - Waechter, Randall L.; Wekerle, Christine; Leslie, Bruce; Goodman, Deborah; Wathen, Nadine; Moody, Brenda (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2009)
This paper presents one model for building and sustaining a research partnership between researchers and professional staff in child protection (CPS) agencies. The Maltreatment and Adolescent Pathways (MAP) study was designed to assess the health and well-being of the population of adolescents involved in the child welfare system of a major urban area. The study involved the collaboration between university based researchers and a range of child welfare staff, from administration to front-line workers. A key factor supporting collaboration was reciprocity with expertise, with CPS practitioner knowledge yielding intervention-relevant study queries and constructs, and researcher knowledge on health content and best practices yielding tailored training opportunities and increased climate for knowledge uptake. The MAP study combined a Participatory Action Research (PAR) model with a traditional, scientific positivist model, including the scientific elements of standardized measures, explicit evaluation of the participatory process, and research impact on the community members. This study: 1) provides information on the process of creating effective researcher-CPC agency partnerships, 2) considers key ethics issues, such as the participant’s reactivity to research of child welfare- involved clients, and 3) examines the implications of implanting a PAR approach in research with Aboriginal CPS agencies, as per the required use of the Canadian Institutes of Health Research (CIHR) Guidelines for Health Research Involving Aboriginal People for future community- university partnerships.